THE INFLUENCE OF COMPENSATION, MOTIVATION, AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF EMPLOYEES AT PT. CITRA PALU MINERALS IN POBOYA VILLAGE, PALU - Amier, Amran Nawir; Thahir, Harifuddin; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to analyze the simultaneous or partially influenced variables of compensation, motivation, and organizational commitment on the performance of employees at PT. Citra Palu Minerals (CPM) in Poboya Village, Palu, Central Sulawesi. The research used a descriptive research type with a quantitative approach. The research sample used stratified random sampling. The type of data used in this research is quantitative which is collected through observation, questionnaires, and documentation then analyzed using multiple linear regressions. The results of the research show that the variables of motivation, compensation and organizational commitment influence the performance of employees at PT. Citra Palu Minerals (CPM) in the Poboya Village, Palu simultaneously or partially. The significance value in the simultaneous and partial test obtained is smaller than the value of the level of significance (∝=0,05). Keywords: Compensation, Motivation, Organizational Commitment and Performance.